2019
DOI: 10.1155/2019/9827147
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Regulates the Expression of Tumor Glycosaminoglycans and Increases the Metastatic Potential of Breast Cancer

Abstract: Galectin-3 (Gal-3) is a multifunctional β-galactoside-binding lectin that once synthesized is expressed in the nucleus, cytoplasm, cell surface, and extracellular environment. Gal-3 plays an important role in breast cancer tumors due to its ability to promote interactions between cell-cell and cell-extracellular matrix (ECM) elements, increasing tumor survival and metastatic dissemination. Still, the mechanism by which Gal-3 interferes with tumor cell migration and metastasis formation is complex and not fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Recent studies have shown that LGALS3 is tightly associated with several malignancies such as Hodgkin’s lymphoma ( Koh et al, 2014 ), acute myeloid leukemia ( Cheng et al, 2013 ), and HCC ( Song et al, 2014 ). More importantly, LGALS3 could increase the metastatic potential of breast cancer, might accounting for the metastatic potential of HCC ( Pereira et al, 2019 ). Through validation in western blot and IHC assays, we found that the protein expression of these five hub genes was in accordance with their mRNA expression in HCC patient tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that LGALS3 is tightly associated with several malignancies such as Hodgkin’s lymphoma ( Koh et al, 2014 ), acute myeloid leukemia ( Cheng et al, 2013 ), and HCC ( Song et al, 2014 ). More importantly, LGALS3 could increase the metastatic potential of breast cancer, might accounting for the metastatic potential of HCC ( Pereira et al, 2019 ). Through validation in western blot and IHC assays, we found that the protein expression of these five hub genes was in accordance with their mRNA expression in HCC patient tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Both experiments showed that intracellular Gal-3 tends to reduce the metastatic potential of B16 cells, at least in part by negative regulation of the integrin-b3 (94). In contrast, working with the 4T1 murine breast carcinoma model, Pereira et al showed that Gal-3 tends to increase the metastatic potential of these malignant cells with a concomitant reduction of the surface expression of syndecan-1 and a greater expression of chondroitin sulfate proteoglycans such as versican (95). Apparently with regard to Gal-1, published data are more consistent suggesting that it frequently enhances the metastatic potential of malignant cells.…”
Section: Influence On Cell Motility and Metastatic Processesmentioning
confidence: 99%
“…Elevated levels of Gal-3 are typically associated with a pro-metastatic tumour phenotype; however, Pereira et al have reported that reduced Gal-3 expression during breast cancer progression correlated with increased metastasis of 4T1 murine breast cancer cells to the bone marrow. 77 …”
Section: Evading Apoptosis and Cell Deathmentioning
confidence: 99%